WRITING ANXIETY AS A PREDICTOR OF ACADEMIC DISHONESTY AMONG UNDERGRADUATES IN ENUGU STATE, NIGERIA - Nwebiem, Patience C. (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2022)
Over the years, English as a second language has assumed an essential part of Nigeria's educational system and represents the most crucial subject in the school curriculum. Consequently, English has been fraught with several challenges encompassing speaking, reading, listening, and writing. Indeed, writing skill is a complex part of English that impedes education development in many instances. The present study examined writing anxiety as a possible correlate of academic dishonesty among undergraduates. Two hundred and forty-eight undergraduates enrolled in a public higher institution in Enugu state participated in the study. A cross-sectional research design was employed, and the analysis established a statistically significant interaction between writing anxiety and academic dishonesty F (1,246), 31.42, P<.000. Most importantly, the R2 indicated that writing anxiety contributed about 13.3% of the variance in academic dishonesty among the respondents. The study concludes that writing anxiety is a significant determinant of dishonest behavior in undergraduates.